Estudo de combustão seca e molhada nas configurações de poços verticais e THAI - Rodrigues, Francisco Leandro de Oliveira (2012)
We study, through numerical simulation, the response of oil and gas reservoirs subjected to in situ combustion, dry and wet. We use vertical and THAI Toe-to-Heel Air Injection well configurations. For this study it is used a numerical simulator for thermal processes, the STARS by CMG group. In the configuration of vertical wells it is used an arrangement of the type 1/4 of five-spot that consists of two vertical wells localized at diagonally opposite corners from a horizontal parallelepiped. In this , there is an initial process, called preheating, that makes the cyclic steam injection. Later, it made the air injection to generate the combustion front. Already in the configuration THAI, there is a vertical well, responsible for the injection of air to generate the combustion and a horizontal well, responsible for production. In two configurations are verified the productions and rates of oil, water and gas and water-oil and gas-oil ratios. The purpose of this work is to analyze the performance of these configurations. The results show that wet combustion is more effective than dry combustion for both well configurations. Although, the wet combustion process has produced far more water than dry combustion process, a negative factor, their relative performance to the factor of oil recovery was betther.